2013
DOI: 10.1097/mpg.0b013e3182a02608
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori Infection by Means of Reduced‐Dose 13C‐Urea Breath Test and Early Sampling of Exhaled Breath

Abstract: Low-dose ¹³C-UBT with early sampling is accurate for diagnosing H pylori infection in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
3
12
0
2
Order By: Relevance
“…Yang et al from Korea, indicated sensitivity and specificity of 97.1% and 96.4% correspondingly (30) . In another study on 129 children age 2.1-19 years, sensitivity and specificity of 13 C-UBT were more than 90% (25) . In the study by Kawakemi et al on 75 children aged 6 months to 8 years, sensitivity and specificity of UBT were 96.8% and 93.2% respectively (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al from Korea, indicated sensitivity and specificity of 97.1% and 96.4% correspondingly (30) . In another study on 129 children age 2.1-19 years, sensitivity and specificity of 13 C-UBT were more than 90% (25) . In the study by Kawakemi et al on 75 children aged 6 months to 8 years, sensitivity and specificity of UBT were 96.8% and 93.2% respectively (17) .…”
Section: Discussionmentioning
confidence: 99%
“…However, biopsy is an invasive and tedious procedure, requiring endoscopy that is prone to missing small lesions and making the patient uncomfortable. Noninvasive tests have also been developed, such as the urea breath test (UBT)910, IgG serology11, immunoblot12 and antigen stool detection13. UBT, based on the activity of urease of H. pylori , is the most sensitive and noninvasive test among these traditional methods.…”
mentioning
confidence: 99%
“…The cross‐sectional studies on H. pylori infection in symptomatic children as detected by histology are summarized in Figure [references: ] . H. pylori prevalence estimates vary greatly (3%‐76%) with an overall random‐effects regression model estimate of 39% (95% CI: 35%‐43%).…”
Section: Resultsmentioning
confidence: 99%